2023
DOI: 10.3389/feduc.2023.1159864
|View full text |Cite|
|
Sign up to set email alerts
|

Factors contributing to university dropout: a review

Abstract: IntroductionDropout is one of the problems that the university education system has to face every year. The educational community is involved in the reasons for its trajectory as a social problem, which does not exempt any student in the world. Its study and improvement of the education system is a key element in changing the course of university dropout and alleviating its rapid growth in society.MethodologyUsing a quantitative and qualitative methodology, an attempt is made to provide answers to the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Some other factors such as "Individual" are also of concern, occupies the second place, they are the student's own conditions, the variables found correspond to the student's motivation, insecurity, family and emotional problems, health; these findings are also related to the researchers De la Cruz-Campos et al (2023;Liza & García-Salirrosas, (2022), also consider the new environment, new challenges, adding the Covid-19 pandemic as another variable for desertion, these authors also mention the "economic" factor in their studies. The factor "Institutional" we have Lorenzo-Quiles et al (2023), who mentions that institutional policies, support for the student body in academics are determinants for the detention of students, there are also other variables, as noted by Mellado et al, 2018. However, the "economic" factor occupies fourth place in the present study, unlike the authors mentioned above, who mentioned it as one of the main factors in the decision to leave the classroom.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some other factors such as "Individual" are also of concern, occupies the second place, they are the student's own conditions, the variables found correspond to the student's motivation, insecurity, family and emotional problems, health; these findings are also related to the researchers De la Cruz-Campos et al (2023;Liza & García-Salirrosas, (2022), also consider the new environment, new challenges, adding the Covid-19 pandemic as another variable for desertion, these authors also mention the "economic" factor in their studies. The factor "Institutional" we have Lorenzo-Quiles et al (2023), who mentions that institutional policies, support for the student body in academics are determinants for the detention of students, there are also other variables, as noted by Mellado et al, 2018. However, the "economic" factor occupies fourth place in the present study, unlike the authors mentioned above, who mentioned it as one of the main factors in the decision to leave the classroom.…”
Section: Discussionmentioning
confidence: 94%
“…Several previous review studies on student dropout have been found; for example, from an international point of view, they indicate that there are high levels of students who drop out of Spanish universities, within the first year (De la Cruz-Campos et al,2023;Lorenzo-Quiles et al,2023; as well as in other countries worldwide (Aina et al,2022;Rodríguez-Hernández et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In their review, the authors miss the research's focus on the involvement of training companies and vocational schools. With regard to dropout from university, it seems promising to learn more about the mechanisms of soft factors, such as their motivation or self-perception and integration in the academic environment [34]. The topics found in the YouTube comments can, therefore, provide clues on which other factors could play a role in dropout that have not yet been covered in previous research.…”
Section: Dropout Causes As Potential Topics In the Commentsmentioning
confidence: 99%
“…It is conceivable that these factors are being discussed in the comments. The family background category includes aspects such as socio-economic status or ethnicity, which influence the dropout risk [32][33][34]. Previous school performance also influences dropout rates.…”
Section: Dropout Causes As Potential Topics In the Commentsmentioning
confidence: 99%